2010 IEEE Information Theory Workshop 2010
DOI: 10.1109/cig.2010.5592866
|View full text |Cite
|
Sign up to set email alerts
|

A renormalization group decoding algorithm for topological quantum codes

Abstract: Topological quantum error-correcting codes are defined by geometrically local checks on a two-dimensional lattice of quantum bits (qubits), making them particularly well suited for fault-tolerant quantum information processing. Here, we present a decoding algorithm for topological codes that is faster than previously known algorithms and applies to a wider class of topological codes. Our algorithm makes use of two methods inspired from statistical physics: renormalization groups and mean-field approximations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 12 publications
1
63
0
1
Order By: Relevance
“…Nevertheless, the main disadvantage of the MWPMA is that it is not suitable for qudit surface codes with d > 2. For these reasons, the development of alternative decoding algorithms is currently a very active research area [14,15,[22][23][24][25][26][27].…”
Section: Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the main disadvantage of the MWPMA is that it is not suitable for qudit surface codes with d > 2. For these reasons, the development of alternative decoding algorithms is currently a very active research area [14,15,[22][23][24][25][26][27].…”
Section: Overviewmentioning
confidence: 99%
“…5, where we find a threshold value of p (2) th = 0.0215 ± 0.0006. This allows us to directly compare our decoder with other fault-tolerant qubit decoders; for example, the soft-decision renormalization-group decoder by Duclos-Cianci and Poulin achieves a threshold of p (2) th = 0.019 ± 0.004 [22].…”
Section: Thresholds Estimation and Percolation Limitationmentioning
confidence: 99%
See 1 more Smart Citation
“…This additional complication in the structure of the syndromes makes the problem of finding optimal decoders for color codes more difficult. There are decoders based on the renormalization group [27], and decoders which decompose the decoding problem into multiple instances of minimum-weight perfect matching [19]. Using a non-scalable decoder based on integer programming, thresholds of 10.56% (data-only errors), 3.05% (data & syndrome errors) and 0.082% (circuit-based errors) have been obtained for the color code on the square-octagon lattice [16].…”
Section: Decodingmentioning
confidence: 99%
“…However, in the case of surface codes, it has been shown that some proposed renormalization-group (RG) algorithms can be generalized to qudit codes in a straightforward manner [8,51]. Moreover, recent work for the 3D fault-tolerant implementation of the qudit surface code using a hard-decision RG decoder [9] suggests that adaptations of such algorithms for higher spatial dimensions should be possible, however, the error correction thresholds would likely be degraded as the spatial dimension increases due to the larger stabilizer generators.…”
Section: Error Detectionmentioning
confidence: 99%